Currency and Interest Rate Effect on Financial Ratios: Technology Case on ISE - (:unkn) unknown (IGI GLOBAL, 2014)
The purpose of this study is to analyze the effects of currency and interest rates on selected financial ratios of technology firms. In a developing country, as an economic indicator, currency and interest rates have crucial impact on technology firms' financial statements. The authors selected financial ratios from seven technology companies that were included in the technology index on Istanbul Stock Exchange (ISE) between the years 2001 and 2010. Findings suggest that Dollar and Euro-Turkish Lira currency affect the current ratio, Euro-Turkish Lira currency only affects the acid-test ratios and net working capital turnover, and Dollar currency and interest rates both have an effect on total asset turnover. Net profit margin ratio is only affected by interest rates changes. This analysis helps technology sector managers and shareholders to forecast the changing currency and interest rates in order to optimize their financial statements.
Keywords: RESEARCH-AND-DEVELOPMENT; FIRM PERFORMANCE; PANEL-DATA; SOFTWARE INDUSTRY; CAPITAL STRUCTURE; EMERGING MARKETS; INVESTMENT; CRISES; CONSTRAINTS; VOLATILITY